Environmental management for collections alternative conservation strategies for hot and humid climates - Maekawa, Shin 1952-; Beltran, Vincent L. 1974-; Henry, Michael C. 1949- (Tools for conservation, 2015)
"A practical guide to the conservation of museum and other cultural heritage collections in hot and humid climates"...Provided by publisher